The Learning Crisis in the United States Three Years After Covid-19 - Harry Anthony Patrinos; Maciej Jakubowski; Tomasz Gajderowicz (Global Labor Organization (GLO), 2025)
The COVID-19 pandemic caused widespread disruptions to education, with school closures affecting over one billion children. These closures, aimed at reducing virus transmission, resulted in significant learning losses, particularly in mathematics and science. Using United States data from TIMSS, this study analyzes the impact of school closure on learning outcomes. The losses amount to 0.36 SD for mathematics and 0.16 SD for science. The declines are similar across grades. The average decline in mathematics performance among U.S. students is substantially greater than the global average. n science, the decline observed among U.S. students does not significantly differ from the global trend. Girls experienced greater deviations from long-term trends than boys across both subjects and grade levels, reversing long term trends that once favored girls. Robustness checks confirm that pandemic-related school closures caused the decline in mathematics, while the downturn in science had already begun before COVID-19.
Keywords: E24; J11; J17; J31; 330; Pandemics; human capital; returns to education; labor markets; COVID-19